Abandono familiar y afectación psicosocial en los adultos mayores de la Estancia Municipal Los Huilcos de la parroquia Vilcabamba, en la actualidad - Armijos Rosillo, Karla Lisbeth (2025)
The main objective of this thesis is to analyze family abandonment and its impact on the psychosocial affectation of older adults in the Vilcabamba parish. Through a qualitative and quantitative approach, we explored the family dynamics, the factors that contribute to abandonment and the emotional, social and psychological consequences in this vulnerable population. Common causes of family abandonment were identified, such as migration, economic precariousness, intergenerational conflicts and lack of social support. It also showed that abandonment has significant repercussions on the self-esteem, mental health and social isolation of older adults, increasing risks such as depression, anxiety and feelings of loneliness. The research underscores the need to implement public policies, community intervention programs and family strategies to strengthen intergenerational ties and promote the integral well-being of older adults. In addition, it highlights the importance of sensitizing society on the rights and value of this population in the current social context, among the results obtained we can evidence the psychosocial affectation of older adults which has a negative impact on the quality of life of this age group, leading to generate even medical conditions, which is why it is concluded that the impact generated by family abandonment is a significant factor in the quality of life of this age group, which is why it is concluded that the impact generated by the abandonment of the family is not only a problem for the elderly, but also for the elderly